The problem definition of selection of the efficiency control index of TCS - Холодкова, Анна Валерьевна (Eastern-European Journal of Enterprise Technologies, 2012)
This article represents the process of choosing the parameters for a system of dynamic control of TKS. The effectiveness of different options for constructing a system of dynamic control of TСS